Análisis jurídico de la sanción del tipo penal asesinato cometido por los adolescentes en conflicto con la ley penal en el cantón esmeraldas. - Quinteros, José H. (2022)
The present studies investigation it maintained the purpose of Analyzing artificial and doctrinariamente the sanction to the adolescents in conflict with the criminal statute for the murder crime in the canton Emeralds; consequently. The utilized methodology to be characterized to be mixed (quantitative and qualitative), linking a scientific investigation, of field and bibliographical, the descriptive, deductive methods were also used-inductive and the logical one; you work with a sample of 32 people, distributed: 2 judges and 30 professionals of the right. It was applied surveys and interviews to those involved in the study object. The results obtained in this investigation, existing the nonfulfillment of the principle of proportionality in the application from the hardships to the adolescent offenders, he/she also stands out that the sanction should be in agreement to what the Art.40 of the COIP specifies, whereas they are determined that these offenders should purge a pain that justifies the murder crime, and this is added that it should be reformed the Code of the Childhood and the Adolescence, so that they become hard the sanctions and the hardships, that is to say, working the adolescent offender that has made the crime of aforethought murder and treachery. As outstanding conclusion it is exposed that the murder crime is tipificado in the Art. 40 of the COIP, where it establishes a penal sanction 22 years old prison for biggest mature people to 18 years, adding the added difficulties, however, for the adolescents that make this same illicit fact, they will be sanctioned with the special legislation, Code of the Childhood and the Adolescence, and alone it rules that he/she is applied measured 4-8 year-old socioeducativas.